Kehidupan Sosial Waria di Tengah Masyarakat Muslim Yogyakarta - Alif Nuur Kholifah; Sutinah .; Emy Susanti (Universitas Wijaya Kusuma Surabaya, 2023)
AbstractThe social life of waria is often marked by challenges and discrimination from the surrounding community. In social spaces, the existence of waria is still difficult to accept by some communities, especially in conservative environments. This often leads to difficulties in finding employment and accessing adequate healthcare services. As a result, some waria are forced to become sex workers who are vulnerable to HIV/AIDS. Nevertheless, there are also waria communities that actively advocate for their rights and form supportive social networks. This article is the result of qualitative research, using a case study approach. The findings of this study indicate that the social life of waria in the Gowongan Lor Muslim community still faces challenges. Their presence still generates both support and opposition, largely due to their gender identity and activities that are considered deviant, such as engaging in sex work and being vulnerable to HIV/AIDS. Keywords: Social life, waria, sex worker, HIV/AIDS.